Perception of hotel industry partner towards the vocational high school students' internship performance - Samsiwihati Samsiwihati; Bambang Nur Achsan; Budi Santoso (Universitas Ahmad Dahlan, 2021)
This research is motivated by the fact that there are still many graduates of the hotel expertise vocational school who have not been employed in the hotel industry because the competencies possessed by the graduates are not in line with the market needs. This study aims to: (1) describe the students' performance in the internship program of SMKN 1 Sewon; (2) analyze perceptions of the partner hotel industry on the internship performance of SMK 1 Sewon Bantul students. This research method used a qualitative descriptive approach. The research subjects consisted of seven hotel industries in Yogyakarta. The data sources used primary and secondary sources. Primary data sources were obtained from interviews. Secondary sources were obtained from literature, observation, and documentation. The sampling technique used purposive sampling. The data validity used triangulation, and the data analysis used a qualitative approach by Milles and Huberman. The results of the study concluded that: (1) the performance of internship in the hotel expertise program of SMKN 1 Sewon Bantul was in the excellent category; (2) The perception of the hotel industry partners on the internship performance of SMKN 1 Sewon Bantul students was very good. It was shown by the summary of the results obtained by the assessment in the category of very good with an average of 96.00%. It means that the hotel managers perceive the performance of intern students are categorized as very good and good starting from appearance, speech, mastery of competence, attendance, completing tasks, obeying an order, communication, using tools or facilities, and completing tasks according to procedures and on time.